From Inauguration to Commercialisation: Incremental yet Contested Transitions Redefining the National Interests of International Degree Programmes in Finland - Suvi Jokila (Informa UK Limited (Routledge, Taylor & Francis Group), 2022)
International degree programmes (IDPs) act as focal instruments for the internationalization of higher education in many non-English–speaking countries serving a variety of national objectives, with the commercial objective becoming increasingly common. This study analyses how IDPs have developed in one Nordic country, Finland, from a marginal activity into programmes that underpin commercially oriented definition of internationalization. The data consists of key policy texts and administrative documents analysed to trace policy changes. The findings suggest that IDPs have developed from the internationalisers of the universities and development aid to recruitment channels for bringing skilled labour to Finland and promoting education export. Having global similarities in their development, policy changes towards commercial understandings of IDPs has been contested, particularly regarding funding, which relates to equality principles in the Finnish higher education system. These shifts have had repercussions for the idea of IDPs, universities and students.